A biomechanical investigation of the static stabilisers of the glenohumeral joint in the dog - Gray, M. J.; Lambrechts, N. E.; Maritz, N. G. J.; Joubert, K. E. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The aim was to determine the relative contribution of the glenohumeral ligaments/joint capsule complex and the limited joint volume/adhesion-cohesion (LJV/AC) mechanisms to the static stability of the canine glenohumeral joint (GHJ). The GHJ of 32 complete cadaver specimens were manipulated to determine the presence of gross laxity (>2mm translation) at joint angles of 150°, 135° and 90°. Following the removal of the peri-articular muscles, laxity was measured by applying a 15N force to the scapula in a variety of directions whilst the humerus was fixed to a jig. This was repeated for the abovementioned angles in intact joints and after venting and flushing to eliminate the LJV/AC mechanisms. Results of clinical palpation and biomechanical studies were compared. Manipulation revealed a marked variation between joints although there was a tendency for progressive laxity as the joint was flexed. This finding was supported by the biomechanical study that also demonstrated no significant difference between intact and vented joints except in a cranio-caudal direction at 135° and 90°, and in a medial/lateral direction at 135°. Static stabilisers permitted a wide range of motion. Individual clinical palpations did not correlate well with biomechanical findings. Manipulation was difficult to perform and is unlikely to be a reliable method for determining subtle joint laxity. The static stabilisers do not appear to play a significant role in providing joint constraint during normal range of motion (except extension). Diagnoses of pathological laxity attributable to the static stabilisers should be made with caution and surgical treatments should take cognizance of the above-mentioned biomechanical features.
Keywords: Glenohumeral joint; dog; shoulder; static stabilisers; limited joint volume